2006
DOI: 10.2353/ajpath.2006.060185
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α and Interleukin-1β Regulate Interleukin-8 Expression in Third Trimester Decidual Cells

Abstract: Chorioamnionitis is associated with intense neutrophil infiltration of the decidua. We therefore determined whether chorioamnionitis enhances decidual interleukin-8 (IL-8) expression and examined cytokine-regulated decidual IL-8 expression. Decidua from chorioamnionitis-complicated pregnancies, but not term controls, displayed marked IL-8 immunohistochemical staining and a dense neutrophil infiltrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 42 publications
(29 reference statements)
1
57
0
2
Order By: Relevance
“…4 free membranes, chorionic plate, and umbilical cord. Consistent with this acute inflammatory response, our laboratory 29 and that of Dudley 30 found that in cultured term DCs IL-1␤ enhances expression of well established neutrophil chemoattractants and activators such as IL-8, epithelial neutrophil-activating peptide (ENA-78), growthrelated oncogene-␣ (Gro-␣), and granulocyte-chemotactic protein-2 (MCP-2).…”
Section: Il-6 Regulation In Decidual Cells 1761mentioning
confidence: 58%
See 1 more Smart Citation
“…4 free membranes, chorionic plate, and umbilical cord. Consistent with this acute inflammatory response, our laboratory 29 and that of Dudley 30 found that in cultured term DCs IL-1␤ enhances expression of well established neutrophil chemoattractants and activators such as IL-8, epithelial neutrophil-activating peptide (ENA-78), growthrelated oncogene-␣ (Gro-␣), and granulocyte-chemotactic protein-2 (MCP-2).…”
Section: Il-6 Regulation In Decidual Cells 1761mentioning
confidence: 58%
“…41 Moreover, inhibition of IL-6 expression by MPA in cultured term DCs described in the current study suggests a mechanism by which maintenance of high circulating progesterone levels blocks conversion of acute to chronic inflammation in the decidua. The specificity of this progestin-mediated inhibition of IL-6 expression is indicated by our observation that MPA did not affect expression of either GM-CSF, 40 M-CSF, 41 MCP-1, 42 or IL-8 29 by the DCs. The severe pathological complications associated with monocyte-associated chronic inflammation in the decidua described in the Alabama Preterm Birth Study were not experienced by the majority of patients with CAM in Figure 8.…”
Section: Il-6 Regulation In Decidual Cells 1761mentioning
confidence: 75%
“…Bacterial-derived lipopolysaccharides enhance IL-1␤ and TNF-␣ expression in human decidual cells and decidual macrophages (9,10). Our laboratory found that both cytokines increased expression of neutrophil chemotactic and activating chemokines in term decidual cell monolayers (11). Neutrophils are the predominant immune cell type in the decidua during CAM and deciduitis.…”
mentioning
confidence: 79%
“…at ASPET Journals on May 11, 2018 dmd.aspetjournals.org chorioamnionitis (Lockwood et al, 2006) as well as in amniotic fluid and cord blood from women with intrauterine infection. We found a significant fold increase in IL-8 mRNA expression in placentas in PTLI, whereas there were no differences in placentas in preterm versus term pregnancy as demonstrated in comparisons between PTLNI and TL and TNL (Fig.…”
Section: Transporter Expression and Pregnancy Conditionmentioning
confidence: 99%